Preferentially Disrupted Core Hubs Within the Default-Mode Network in Patients With End-Stage Renal Disease: A Resting-State Functional Magnetic Resonance Imaging Study - Ma, Chi; Tian, Fen; Ma, Min-ge; Su, Hua-wei; Fan, Jian-cong; Li, Zhan-hui; Ren, Yan-de (Frontiers in Neurology, 2020)
Neuroimaging evidence implies that cognitive impairment in patients with end-stage renal disease (ESRD) is related to the disruption of the default-mode network (DMN). The DMN can be divided into three functionally independent subsystems, which include the cortical hubs subsystem (consisting of the posterior cingulate cortex [PCC] and the anterior medial prefrontal cortex [aMPFC]), the dorsal medial prefrontal cortex (dMPFC) subsystem and the medial temporal lobe (MTL) subsystem. However, it is unknown how the functional connectivity (FC) in DMN subsystems is differentially impaired in ESRD. This prospective study was carried out at the Affiliated Hospital of Medical College of Qingdao University, China, between August 2018 and July 2020. Thirty-two ESRD patients and 45 healthy controls (HCs) were recruited for this study and received resting-state functional magnetic resonance imaging (rs-fMRI) scanning, and FCs on predefined regions of interest (ROIs) were individually calculated in three DMN subsystems using both ROI- and seed-based FC analyses to examine FC alterations within and between DMN subsystems. The two-sample t test was used for the comparisons between groups. We also tested the associations between FC changes and clinical information using Pearson correlation analysis. The results demonstrated that ESRD patients, compared to HCs, exhibit reduced FC specifically within the cortical hubs and between the DMN hubs and two subsystems (the dMPFC subsystem and MTL subsystems). Moreover, FC values between the aMPFC and PCC were positively correlated with creatinine and urea levels in ESRD patients. Our results suggest that the cortical hubs (PCC and aMPFC) are preferentially disrupted and that other subsystems may be progressively damaged to a certain degree as the disease develops.